Penerapan Diversi terhadap Anak Sebagai Pelaku Tindak Pidana Pencurian di Wilayah Hukum Kepolisian Resort Kota Jambi - Badri, Mhd.; Sumaidi, Sumaidi; Iswanto, Reza (Wajah Hukum, 2024)
Many children are now involved in criminal acts, including theft, so the solution needs to be done through diversion. The aim of the research is to understand and analyze the application of diversion to children as perpetrators of criminal acts in the jurisdiction of the Jambi City Resort Police and the obstacles in criminal law in the application of diversion to children as perpetrators of criminal acts in the jurisdiction of the Jambi City Resort Police. For this reason, this research uses a legal sociology approach with an activity design for 6 months whose scope or object in this research focuses on the application of diversion to children who are perpetrators of criminal acts of theft in the Jambi New City Sector Police. The main materials and tools used in this research are primary legal materials that come from the field and secondary legal materials that come from the library, then the place used in this research is the Jambi New City police sector so that the data collection technique is in the form of direct interviews with respondents. which produces an analysis technique, namely qualitative analysis. The results of this research are that diversion has not been applied to children as perpetrators of criminal acts by the Jambi City Resort Police, but there are still several obstacles so that diversion is often failed in achieving this and obstacles in implementing diversion against children as perpetrators of criminal acts of theft in the jurisdiction of the Sector Police. Kota Baru Jambi is where the victim does not want to carry out diversion because they still prioritize the deterrent effect on the perpetrator.